Effect Of Viscosity, Application Rate And Incidence Of Dust On The Adhesion Of A League Irrigation Of Asphalt Layers Evaluated With The Nlt-382/08 Test - Burbano, Jorge Luis Argoty; Ante, Jaime Rafael Obando (Migration Letters, 2023)
The increase in traffic levels on the country’s roads requires robust asphalt pavement structures with thicker folders (Portillo, 2020) that in most cases must be built in more than one layer: requiring joining through a league irrigation, which provides the effective adhesion between layers of pavement (LanammeUCR, 2019). Garter irrigation is critical to transfer the stresses induced by transit loads to the structure, precisely this concept has been the subject of extensive research over time, to try to establish the correct variations and mitigate the factors that influence its degree of adhesion (Dorado & Rosero, 2018). Various types of problems occur on asphalt pavements, due to the lack of adhesion between the asphalt tread layers (González, 2018). For this reason, the adhesion resistance of the interface was studied in the laboratory by means of the test of the Laboratorio de Caminos de Barcelona (LCB) of the Spanish standard NLT 382/08, which evaluates adhesion by means of a shear test between bonded layers. The aim of this study was to identify the adhesion behavior of bituminous layers in a rubber irrigation, using CRR-60 and CRR-65 fast-breaking cationic emulsions and stone aggregates from the municipality of Pasto. This work considered the conditions of viscosity, application rate and dust as an external pollutant, as well as determined the maximum load and the resistance to shear stress generated by the asphalt emulsion at the interface between the bonded asphalt layers. Finally, the study established that the application rates are similar. The best performing binder was the CRR-65 fast-breaking cationic emulsion, as well as a decrease in shear stress resistance with the presence of dust.